Development of Control System of Financial and Economic Results of an Enterprise - Borisovna Frolova, Victoria; Vladimirovna Dmitrieva, Olga; Aleksandrovich Biryukov, Vladimir; Mikhailovna Avramenko, Galina; Anatolievich Lebedev, Konstantin (International Journal of Engineering and Technology, 2018)
The paper presents the proposals for the development of control system of financial and economic results of an enterprise. It was proved that teamwork, corporate culture and high competence of the participants create the necessary conditions for the formation of new thinking and highly professional action. It was found that a company should create the atmosphere of creativity and necessary change including the removal of barriers to the team interaction, the improvement of teamwork vertically, horizontally and throughout the management structure. It was determined that models and methods as elements of the result management system are the main and formative components of the financial and economic results control system of enterprises itself since the functioning of the entire system and each of its elements depends on the choice of specific management models and methods or their combination
Keywords: development; system; management; financial and economic results; enterprise; decision; efficiency; activity; technology; method.